Loss-of-Function Mutation of Soybean R2R3 MYB Transcription Factor Dilutes Tawny Pubescence Color - Yan, Fan; Githiri, Stephen M.; Liu, Yajing; Sang, Yu; Wang, Qingyu; Takahashi, Ryoji (Frontiers in Plant Science, 2020)
Pubescence color of soybean is controlled by two genes, T and Td. In the presence of a dominant T allele, dominant and recessive alleles of the Td locus generate tawny and light tawny (or near-gray) pubescence, respectively. Flavones, responsible for pubescence color, are synthesized via two copies of flavone synthase II genes (FNS II-1 and FNS II-2). This study was conducted to map and clone the Td gene. Genetic and linkage analysis using an F2 population and F3 families derived from a cross between a Clark near-isogenic line with light tawny pubescence (genotype: TT tdtd) and a Harosoy near-isogenic line with tawny pubescence (TT TdTd) revealed a single gene for pubescence color around the end of chromosome 3. Genome sequence alignment of plant introductions revealed an association between premature stop codons in Glyma.03G258700 (R2R3 MYB transcription factor) and recessive td allele. Cultivars and lines having near-gray or light tawny pubescence and a gray pubescence cultivar with td allele had premature stop codons in the gene. These results suggest that Glyma.03G258700 corresponds to the Td gene. It was predominantly expressed in pubescence. Compared to a tawny pubescence line, a near-isogenic line with td allele produced extremely small amounts of transcripts of Glyma.03G258700, FNS II-1, and FNS II-2 in pubescence. The promoter of FNS II-1 and FNS II-2 shared cis-acting regulatory elements for binding of MYB proteins. These results suggest that the wild-type of Glyma.03G258700 protein may bind to the promoter of FNS II genes and upregulates their expression, resulting in increased flavone content and deeper pubescence color. In contrast, mutated Glyma.03G258700 protein may fail to upregulate the expression of FNS II genes, resulting in decreased flavone content and dilute pubescence color. These results strongly suggest that soybean Glyma.03G258700 encoding the R2R3 MYB transcription factor corresponds to the Td gene.